EFFECT OF SPEED-GOVERNOR DEADBAND ON AGC ANALYSIS FOR TWO AREAS THERMAL-THERMAL SYSTEM (Sciences & Technologie. B, Sciences de l'ingénieur, 2003)
Thermal system is present in this paper. The governor deadband nonlinearity is included in the analysis. The model by just changing the controllers can be used to study the response with and without governor deadband. It is shown that the governor deadband nonlinearity has a destabilizing effect on the transient response with deterministic load disturbance. It is found that the proportional integral controller reduces the over shoot and leaves the setting time unchanged with respect to case when using integral controller. It is found that the value of B has an important influence on the transient behavior of AGC.